Improving The Performance Of Industrial-Technical Schools In Egypt In The Light Of Corporate Schools Model: A Qualitative Study - Omar Mohamed M. Morsi (European Scientific Journal, ESJ, 2016)
Corporate schools are no longer a new phenomenon since more organizations are currently moving towards this model for workplace learning. Therefore, the current study aimed at setting a suggested proposal to improve the performance of the industrial technical schools in Egypt in the light of the corporate schools model. This involves examining both the real goals and the problems encountered in the Egyptian industrial-technical education. Moreover, the study examines the corporate school phenomenon by analyzing one example of corporate schools. The current study used a qualitative-analytic method as it suits the nature of the study. The study came down to some results, most important of which are: (1) corporate schools can contribute to overcoming the problems which face the industrial schools; (2) corporate schools are educational entities that serve business strategy. Based on this, the paper concludes with a suggested proposal to improve the performance of the industrial-technical schools in Egypt.